INTESTINAL MICROBIOCENOSIS, FOOD TOLERANCE AND FOOD ALLERGY. CURRENT STATE OF A PROBLEM - S. G. Makarova; M. N. Boldyreva; Т. E. Lavrova; М. I. Petrovskaya ("Paediatrician" Publishers LLC, 2014)
In the review of modern literature the influence of a bacterial factor, first of all - indigenous microflora - on formation of food tolerance and immune answer of a child as a whole is in detail considered. Formation of a microbiocenosis, food and autogenic tolerance happens under the general laws. In this process the primary colonization of intestines and formation of a microflora variety which, as results of the last researches show, comes to an end by 2-4 years of life of a child has special value. In the review the major factors influencing the formation of a child intestinal microbiota both antenatal and postnatal and for the first years of life, and also their interaction are considered. The influence of a bacterial factor on formation of food tolerance and sensibilization processes, and also mechanisms of this influence is in detail discussed. The data on features of a structure of intestinal microflora at children with food allergy including the results of own researches devoted to microbiocenosis at children with food allergy and to development of tactics of management of children with this pathology are provided. The main directions and possibilities of dietary influence on biocenosis structure at children with this pathology are considered.